2004
DOI: 10.1080/08880010490500935
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pediatric Thrombotic Patients in Turkey

Abstract: This study analyzes the data of thrombotic children who were followed up in different pediatric referral centers of Turkey, to obtain more general data on the diagnosis, risk factors, management, and outcome of thrombosis in Turkish children. A simple two-page questionnaire was distributed among contact people from each center to standardize data collection. Thirteen pediatric referral centers responded to the invitation and the total number of cases was 271. All children were diagnosed with thromboembolic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 36 publications
4
31
2
Order By: Relevance
“…To our knowledge, there is only 1 report on the risk factors of thrombosis in Turkish children [7]. However, in this multicenter study that summarized the data of the Society of Turkish Pediatric Hematology, the incidence of childhood thrombosis in Turkey has not been evaluated [7].That study, which consisted of 271 patients, revealed that 4% of the patients with thrombosis were neonates, 12% were infants younger than 1 year, and 17% were adolescents. The authors reported that the median age at the time of the first thrombotic event was 7.0 years (range, 1 day to 38 years).…”
Section: Incidence Of Thrombosismentioning
confidence: 90%
See 2 more Smart Citations
“…To our knowledge, there is only 1 report on the risk factors of thrombosis in Turkish children [7]. However, in this multicenter study that summarized the data of the Society of Turkish Pediatric Hematology, the incidence of childhood thrombosis in Turkey has not been evaluated [7].That study, which consisted of 271 patients, revealed that 4% of the patients with thrombosis were neonates, 12% were infants younger than 1 year, and 17% were adolescents. The authors reported that the median age at the time of the first thrombotic event was 7.0 years (range, 1 day to 38 years).…”
Section: Incidence Of Thrombosismentioning
confidence: 90%
“…The incidence of childhood thrombosis has not been established, although venous thrombosis is the type most common in children [4][5][6][7][8][9]. Arterial thrombosis accounts for 26% of all thrombosis that occurs in children [29].…”
Section: Incidence Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the median age at the time of thrombosis diagnosis in children, Celkan et al reported a median age of 10 years, while Oren et al found this as 7 years, Tavil et al as 10.5 years 10,11,15 . The median age 288 of patients in our study was 5.1 years, which was significantly lower than the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thrombosis was reported to account for 26% of all pediatric thrombosis cases 22 . Although the incidence of arterial thrombosis in children has not been clearly identified in Turkey yet, Oren et al reported an incidence rate of 1.4% 11 .…”
Section: Discussionmentioning
confidence: 99%